Mishnahs Theology of Tithing: A Study of Tractate Maaserot - Jaffee, Martin (Brown Judaic Studies, 2020)
This study is a translation and exegesis of Mishnah ' s Tractate Maaserot (Tithes) and its corresponding tractate of Tosefta . The goal of the volume is to understand the laws of Maaserot as the tractate 's creator(s) intended them to be understood.